AB0413 Hepatitis B Serologic Profile and Reactivation in Rheumatic Patients Treated with Biological Therapies – Single Centre Experience. (10th June 2014) - Romao, V.; Saavedra, M.; Costa, M.; Macieira, C.; Vieira-Sousa, E.; Ramos, F.; Resende, C.; Capela, S.; Barros, R.; Polido-Pereira, J.; Rodrigues, A.; Madruga-Dias, J.; et al.
Abstract : Background: Biologic therapy for rheumatic diseases has been associated with increased risk of latent infections reactivation such as tuberculosis or hepatitis B (HB), due to severe immunosuppression. However, the actual risk of HB reactivation is still unclear regarding the several biologics available, especially in low-incidence countries such as Portugal. Objectives: To evaluate the serologic HB profile of biologic-treated rheumatic patients in a single centre and assess the incidence of HB reactivation. Methods: We retrospectively collected electronically available HB serology of rheumatic patients that ever started biological therapy at our department and we reviewed the clinical course to identify reactivation cases, defined as raising viral load and transaminases. Results: We included 288 patients with available electronic data on HB serologies. Mean age was 43.9±15.7 years (3.1 to 82.3 years), disease duration was 10.9±9.5 years, 63.9% of patients were female and the most common rheumatic disease was rheumatoid arthritis (112, 38.9%), followed by ankylosing spondylitis (76, 26.4%) and psoriatic arthritis (54, 18.8%). As first biologic, 254 patients (88.2%) started anti-TNF agents, 14 (4.9%) rituximab, 11 (3.8%) tocilizumab and 9 patients (3.1%) another biologic. 30 patients (10.4%) eventually stopped biologic treatment. 185 patients (64.2%) were treated with concomitant methotrexate (mean dosage 15.7±5.4mg), 81 (28.1%) with other DMARDs and 169 (58.7%) were treated with corticosteroids (58.7%). All of the 288 patients were HBsAg negative and 23 were anti-HBc positive (9%). The 23 anti-HBc positive patients did not differ significantly from the overall population in terms of age, gender distribution, disease duration, follow-up time, biologic discontinuation or biologic started. No patient received prophylactic antiviral therapy and there were no cases of reactivation or isolated rise in viral load during a cumulative biologic exposure of 1005.6 patient-years (Fig. 1 ). Conclusions: In our cohort, there were no cases of HB reactivation on the 288 patients treated with biologic therapy. Anti-HBc positivity was infrequent, viral load was undetectable in all cases and no chronic HB cases were detected. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4716